Методологія та засоби для адаптивної верстки сучасного веб-застосунку - Філіпенко, А. В. (ХНУРЕ, 2023)
This text emphasizes the importance of creating an adaptive and reliable website layout, and discusses various approaches for achieving this. It mentions the Bem methodology for creating a good HTML structure, as well as alternative approaches like CSS modules and the React framework. The text also highlights the importance of considering factors like relative units of measure and media, and mentions third-party libraries like Bootstrap and Material-Ui for creating websites quickly and easily. Overall, the text provides a comprehensive overview of creating an adaptive and reliable website layout, including the tools and techniques available for developers to use